Application of the Bethesda System for Reporting Thyroid Cytopathology in the Pediatric Population: A Multicenter Study in Asian Countries. Issue 5 (3rd December 2020) - Vuong, Huy Gia; Suzuki, Ayana; Na, Hee Young; Tuyen, Pham Van; Khuy, Doan Minh; Nguyen, Hiep Canh; Jitpasutham, Tikamporn; Abelardo, Agustina; Amano, Takashi; Park, So Yeon; Jung, Chan Kwon; Hirokawa, Mitsuyoshi; et al.
Abstract: Objectives: We aimed to provide the Asian experience with the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) in pediatric thyroid nodules. Methods: Consecutive thyroid fine-needle aspirates (patient age, ≤18 years) were retrospectively collected from 7 tertiary centers in 5 Asian countries. Results: Of 194, 364 thyroid aspirates, 0.6% were pediatric cases (mean age, 15.0 years). Among 827 nodules with accessible follow-up, the resection rate and risk of malignancy (ROM) were 36.3% and 59.0%, respectively. Malignant nodules (n = 179) accounted for 59.7% of resected nodules and 21.6% of all thyroid nodules with available follow-up. Compared with the published adult series, pediatric nodules had a higher resection rate and ROM, particularly in the indeterminate categories. Conclusions: Our study demonstrates that Asian pediatric thyroid nodules had higher ROM than those from adults. The prototypic outputs of TBSRTC may need to be adjusted in the pediatric population.